REMEDIAL AND PHYTOCHEMICAL REVIEW STUDY ON TECOMA STANSL. - BHAT, MANSOOR AHMAD (Innovare Journal of Life Sciences, 2020)
Tecoma stans is a destructive invader that outcompetes natural florain its surroundings. This plant is considered as a modifier species which leads to a decrease in the biodiversity as well as natural resources. It has been planted as an ornamental garden and street plant, but possesses wide range of therapeutic and pharmaceutical applications. All parts (leaves, root, flower, seed, fruit, and bark) of the plant areusedas a remedy for different diseases. As anherbal remedythe plant parts are used for the treatment of diabetes, digestive problems, control of yeast infections, as powerful diuretic, vermifuge, anti-syphilitic, stomach pains and tonic. Preliminary phytochemical screening and isolation of compounds from this plant has revealed the presence of tannins, flavonoids, phenols, anthraquinones, glycosides, alkaloids, quinones and traces of saponins and amino acids. This article summarizesthe data on its medicinal applications and traditional uses.